Common Fixed Point Theorems for a Pair of Self-Mappings in Fuzzy Cone Metric Spaces. (1st April 2019) - Rehman, Saif Ur; Li, Yongjin; Jabeen, Shamoona; Mahmood, Tayyab
Abstract : In this paper, we present some common fixed point theorems for a pair of self-mappings in fuzzy cone metric spaces under the generalized fuzzy cone contraction conditions. We extend and improve some recent results given in the literature.